Impact of neutrophil extracellular traps on fluid properties, blood flow and complement activation - Burmeister, Antonia; Vidal-y-Sy, Sabine; Liu, Xiaobo; Mess, Christian; Wang, Yuanyuan; Konwar, Swagata; Tschongov, Todor; Häffner, Karsten; Huck, Volker; Schneider, Stefan W.; Gorzelanny, Christian (Frontiers in Immunology, 2022)
The intravascular formation of neutrophil extracellular traps (NETs) is a trigger for coagulation and blood vessel occlusion. NETs are released from neutrophils as a response to strong inflammatory signals in the course of different diseases such as COVID-19, cancer or antiphospholipid syndrome. NETs are composed of large, chromosomal DNA fibers decorated with a variety of proteins such as histones. Previous research suggested a close mechanistic crosstalk between NETs and the coagulation system involving the coagulation factor XII (FXII), von Willebrand factor (VWF) and tissue factor. However, the direct impact of NET-related DNA fibers on blood flow and blood aggregation independent of the coagulation cascade has remained elusive. In the present study, we used different microfluidic setups to investigate the influence of neutrophil-derived extracellular DNA fibers on blood rheology and intravascular occlusion. We found that extended DNA fiber networks decelerate blood flow and promote intravascular occlusion of blood vessels independent of the plasmatic coagulation. Associated with the DNA dependent occlusion of the flow channel was the strong activation of the complement system characterized by the production of complement component 5a (C5a). Vice versa, we detected that the local activation of the complement system at the vascular wall was a trigger for NET release. In conclusion, we found that DNA fibers as the principal component of NETs are sufficient to induce blood aggregation even in the absence of the coagulation system. Moreover, we discovered that complement activation at the endothelial surface promoted NET formation. Our data envisions DNA degradation and complement inhibition as potential therapeutic strategies in NET-induced coagulopathies.